2020
DOI: 10.1038/s41598-020-76063-9
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial and angiogenic effect of magnesium oxide in a hydroxyapatite bone substitute

Abstract: Bone graft infections are serious complications in orthopaedics and the growing resistance to antibiotics is increasing the need for antibacterial strategies. The use of magnesium oxide (MgO) is an interesting alternative since it possesses broad-spectrum antibacterial activity. Additionally, magnesium ions also play a role in bone regeneration, which makes MgO more appealing than other metal oxides. Therefore, a bone substitute composed of hydroxyapatite and MgO (HAp/MgO) spherical granules was developed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…HA-Mg and HA-Si showed almost similar weight loss around 1.8%. These results imply that Mg and Si ion substitution does not alter the biostability of scaffolds much, since the amount of substitution is very less compared to other works [26][27][28]. To evaluate the biostability, the synthesized scaffolds were immersed in Tris-HCl at 37 °C for different time intervals of 3, 7, 14 and 28 days of immersion.…”
Section: Resultsmentioning
confidence: 84%
“…HA-Mg and HA-Si showed almost similar weight loss around 1.8%. These results imply that Mg and Si ion substitution does not alter the biostability of scaffolds much, since the amount of substitution is very less compared to other works [26][27][28]. To evaluate the biostability, the synthesized scaffolds were immersed in Tris-HCl at 37 °C for different time intervals of 3, 7, 14 and 28 days of immersion.…”
Section: Resultsmentioning
confidence: 84%
“…Therefore, well-designed artificial periosteum should have the coupling effect of “osteogenesis-angiogenesis”. Some magnesium-containing scaffolds also confirmed the promoting effect of “osteogenesis-angiogenesis” coupling on bone regeneration [ 9 , 16 , 40 ]. A sustainable releasing of Mg 2+ was proved in artificial periosteum we constructed in this project.…”
Section: Discussionmentioning
confidence: 93%
“…PLGA scaffolds with magnesium oxide (MgO) promoted osteogenesis by sustained release of Mg 2+ [ [12] , [13] , [14] ]. MgO nanoparticles have also been shown to promote bone regeneration and angiogenesis [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…94 Coelho et al showed a significant increase in the number of newly formed vessels at the implantation sites of HAp/MgO spherical granules as compared to pure HAp granules. 95 The mechanism of how magnesium promotes angiogenesis has been studied by Gu et al They found that Mg ions could stimulate proliferation and migration of endothelial cells through G protein-coupled receptor pathway. Mg ions entered into the endothelial cells by caveolin-1-mediated endocytosis, diminishing the level of caveolin-1 and enhancing the activity of eNOS, which promoted angiogenesis.…”
Section: Effects Of Magnesium Ions On Bone Tissue Engineeringmentioning
confidence: 99%
“…Angiogenesis plays an important role in bone tissue’s maturation process and development, and in this process, the vascular endothelial growth factor (VEGF) acts as an important mediator. , Yoshizawa et al found that 10 mM MgSO 4 could enhance the expression of VEGF in BMSCs through stimulation of both HIF-1α and HIF-2α . Coelho et al showed a significant increase in the number of newly formed vessels at the implantation sites of HAp/MgO spherical granules as compared to pure HAp granules . The mechanism of how magnesium promotes angiogenesis has been studied by Gu et al They found that Mg ions could stimulate proliferation and migration of endothelial cells through G protein-coupled receptor pathway.…”
Section: Effects Of Magnesium Ions On Bone Tissue Engineeringmentioning
confidence: 99%